Disciplines and Doctorates - Parry, Sharon (Higher Education Dynamics, 2007)
Advice about how to achieve a PhD usually falls short of relevance because the ways of creating and reporting knowledge differ dramatically from one disciplinary field and specialisation to another. Yet supervisors and doctoral candidates alike know that there are certain protocols or parameters, often inexplicit in nature, that govern its achievement and that need to be mastered. This book sets out to explore the nature of these protocols and parameters, linking them to the cognate characteristics of fields of knowledge and to social conventions constraining how new knowledge is reported. 'Disciplines and Doctorates' provides a detailed analysis of the experience of learning to make new knowledge at the level of the research doctorate. It does so from the perspectives of both supervisors and candidates across a range of disciplines in different university settings. It draws principally upon a very large-scale, empirical investigation at a number of Australian universities. It also provides a comparative account of doctoral study in different national systems.